2001
DOI: 10.1002/ijc.1433
|View full text |Cite
|
Sign up to set email alerts
|

DNA adduct levels and DNA repair polymorphisms in traffic-exposed workers and a general population sample

Abstract: Peripheral blood DNA adducts have been considered an acceptable surrogate for target tissues and possibly predictive of cancer risk. A group of 114 workers exposed to traffic pollution and a random sample of 100 residents were drawn from the EPIC cohort in Florence, a population recently shown to present increased DNA adduct levels (Palli et al., Int J Cancer 2000;87:444 -51). DNA bulky adducts and 3 DNA repair gene polymorphisms were analyzed in peripheral leukocytes donated at enrollment, by using 32 P-postl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 28 publications
8
68
1
2
Order By: Relevance
“…[27][28][29] Various explanations are possible for the divergence between these studies and ours. The controversial results might depend partly on differences in the type of DNA damage detected when compared to the specific BPDE-DNA adduct we have measured.…”
Section: Discussioncontrasting
confidence: 85%
“…[27][28][29] Various explanations are possible for the divergence between these studies and ours. The controversial results might depend partly on differences in the type of DNA damage detected when compared to the specific BPDE-DNA adduct we have measured.…”
Section: Discussioncontrasting
confidence: 85%
“…Even though devoid of any known enzymatic activity, XRCC1 is thought to act as a scaffold protein, play a coordinating role for consecutive stages of the BER system (Ladiges, 2006), The XRCC1 Arg399Gln polymorphism is located within the XRCC1 BRCA1 carboxyl-terminal domain (BRCT I) and is hypothesized to have functional significance because it is located within a well-conserved region and encodes a nonconservative amino acid change. However, studies examining its relation with markers of DNA damage or DNA repair function have yielded mixed results, with some studies showing a positive relation (Duell et al, 2002;Qu and Morimoto, 2005) and others observing no relation with the variants (Palli et al, 2001;Pastorelli et al, 2002;Tuimala et al, 2002;Hu et al, 2005;Leng et al, 2005;Laantri et al, 2011 ). In present study we found homozygous variants of XRCC1 Arg399Gln had observably associations with NPC risk.…”
Section: Discussionsupporting
confidence: 42%
“…A few previous studies reported that the 399Gln allele was associated with a higher level of DNA adducts and glycophorin A mutations (Lunn et al, 1999;Matullo et al, 2001a, b), increased sister chromatin exchange frequencies (Duell et al, 2000), or higher sensitivity to ionizing radiation and chemical mutagens (Hu et al, 2001;Wang et al, 2003a, b). However, conflicting results also exist, showing no association between the 399Arg>Gln polymorphism and DNA adduct levels (Matullo et al, 2001a, b;Palli et al, 2001). The reason for this inconsistency may be the result of some study design issues.…”
Section: Discussionmentioning
confidence: 99%